Research methodology for scientific research - Prathapan, K (I.K. International, 2014)
Contents: 1- Perspective of Scientific Research 2- Philosophy of Science 3- Getting started with research 4- Scientific Methodology 5- Data Collection and Analysis 6- Research in Practice 7- Scientific writing 8- Ethics in Research